Estimating the Economic Determinants of Technical Efficiency of Bioenergy in EU-28: An Application of Tobit Analysis - Alsaleh, Mohd; Abdul-Rahim, A.S (Journal of Social Economics Research, 2019)
This study identified the effects of economic factors on technical efficiency (TE) rate in the bio-energy section for the European Union zone (EU-28). A Tobit framework estimation was used to investigate the economic factors of TE rate in the bio-energy sector for the EU-28 zone during the period among 1990 through 2013. The findings point that economic determinants have a significant impact on TE rate of the bio-energy sector in the EU-28 countries. The empirical findings suggest that labor input and gross domestic product (GDP) significantly affected the TE of the bio-energy sector in the EU-28 zone through the duration of this paper. The results obviously inviting governors and politicians to investigate the TE rate of the bio-energy sector within the EU-28 zone. This paper gives further facts and details to the senates of the bio-energy sectors, as they require to get a further comprehension of the impact TE has on bio-energy production execution. In addition, the findings of this paper have suggestions for financiers who concentrates significantly on revenues from their direct-investments.